The Rights of Indigenous Peoples to Harvest Marine Mammals in the Arctic. Perspectives from International Human Rights Law and the Law of the Sea - Woker, Hilde (UiT Norges arktiske universitet, 2015)
In the context of increasing duties to protect and preserve marine biodiversity, and of gaining importance of indigenous rights, this thesis discusses how international law recognizes the rights of indigenous peoples to harvest marine mammals. It takes on both the perspective from a human rights lawyer, as that of a law of the sea scholar. The human rights law perspective is based on the right to self-determination enshrined in the ICCPR and the ICESCR, and the right to culture, as reflected in Article 27 of the ICCPR and general international law. Through the eyes of the law of the sea scholar, indigenous peoples are entitled to harvest marine mammals based on the aboriginal subsistence whaling exemption in the ICRW system, and the “local people” exception to the polar bear hunt prohibition in the Polar Bear Agreement. Although both fields of law recognize an indigenous people’s right to harvest marine mammals, they differ in scope and application. This thesis argues that these two bodies of international law should be used and interpreted complementary to each other.